2020
DOI: 10.53023/p.rasayan-20200315
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Habenaria edgeworthii (Vrddhi) Leaf Extract Conjugated Gold and Silver nanoparticles

Abstract: he antioxidant activity of the leaf extract of Habenaria edgeworthii (commonly known as Vrddhi) has been studied against a long lived 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical at room temperature. Green syntheses of Vrddhi Leaf extract conjugated gold and silver nanoparticles at room temperature have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…3 Antioxidant activities of various parts of Crepidium acuminatum (Jeevak), 4 Roscoea purpurea Sm. (Kakoli), 5,6 Polygonatum cirrhifolium (Mahameda), 7 Habenaria Edgeworthii (Vrddhi) 8,9 and Habenaria intermedia (Rddhi) and their use in the green syntheses of metal nanoparticles have also been reported by us. 10,11 Tremendous medicinal activities of Jeevak (Crepidium acuminatum) have been reported.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…3 Antioxidant activities of various parts of Crepidium acuminatum (Jeevak), 4 Roscoea purpurea Sm. (Kakoli), 5,6 Polygonatum cirrhifolium (Mahameda), 7 Habenaria Edgeworthii (Vrddhi) 8,9 and Habenaria intermedia (Rddhi) and their use in the green syntheses of metal nanoparticles have also been reported by us. 10,11 Tremendous medicinal activities of Jeevak (Crepidium acuminatum) have been reported.…”
mentioning
confidence: 64%
“…(Kakoli), 5,6 Polygonatum cirrhifolium (Mahameda), 7 Habenaria Edgeworthii (Vrddhi) 8,9 and Habenaria intermedia (Rddhi) and their use in the green syntheses of metal nanoparticles have also been reported by us. 10,11 Tremendous medicinal activities of Jeevak (Crepidium acuminatum) have been reported. 12,13,14 Thorough literature search by us have revealed that there is no report of the active chemical constituents of most of the Astavarga plants.…”
mentioning
confidence: 67%
“…5,6 Previous reports from our laboratory have shown that the pseudobulb of Crepidium acuminatum (Jeevak), 78 extract of Roscoea purpurea Sm. (Kakoli), 9,10 Rhizome Extract of Polygonatum cirrhifolium (Mahameda) 11 and, extracts of Habenaria Edgeworthii (Vrddhi) 12 and Habenaria intermedia (Rddhi) 13,14 are rich in antioxidants. Hence, it occurred to us that the fruit extract of Vrddhi may also be rich in antioxidants.…”
mentioning
confidence: 99%
“…Previously we have reported the green synthesis of gold nanoparticles using extracts Jeevak, Kakoli, Mahameda, Rddhi and and Vrddhi. 7,9,11,12,13,28 Hence it occurred to us that the fruit extract of Vrddhi may be utilized for the green synthesis of AuNP conjugated with the fruit extract of Vrddhi (VFAuNPs). For the green synthesis of gold nanoparticles, a fixed concentration (0.40 mM) of Au (III) was reacted with an increasing concentration of the leaf extract (50 g/mL to 800 g/mL).…”
mentioning
confidence: 99%
“…5,6 Previous reports from our laboratory have shown that the pseudobulb of Crepidium acuminatum (Jeevak), 7 extract of Roscoea purpurea Sm. (Kakoli), 8,9 Rhizome Extract of Polygonatum cirrhifolium (Mahameda) 10 and, extracts of Habenaria Edgeworthii (Vrddhi) 11 and Habenaria intermedia (Rddhi) 12,13 are reach in antioxidants. Hence, it occurred to us that the leaf extract of Jeevak may also be rich in antioxidants.…”
mentioning
confidence: 99%